لتعامل بالنقود الرقمية في المنظور الإسلامي - Muhammad Hamma'Adama Ahmad (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2024)
This research aims to show the dealing with digital money in the perspective of the Islamic .The researcher in this section has mentioned the talk about dealing in digital electronic money in the perspective of the Islamic. He mentioned the definition and the concept of money, and its history and types, and singled out the talk about digital electronic money in terms of its concept and history, and between the rule of dealing with it from the sayings of contemporary scientists that clarify the meaning of what is intended, and the position of the researcher in it, and the problem is currently that many people do not know digital electronic money as well as the rule of dealing with it, it has become necessary to find scientific research that shows and shows the legal ruling in dealing with it, and this study is based on combining approaches based on the nature and style of research, and highlighted The methods used and required by the study are the inductive method, the texts, and the analytical method, which analyzes these texts, and explains some strange words and terms if necessary. Then the researcher used the field study to collect data from books and studies, and then analyze these texts and studies from the sayings of contemporary scholars in electronic and digital money, such as the fatwas of the General Authority of Islamic Affairs and Endowments in Dubai, the fatwas of the Palestinian Dar Al-Iftah, the fatwas of the Egyptian Dar Al-Iftah, and others and others. Then the position of the researcher and weighting. This section contained an introduction and four sections, and in conclusion, the researcher shed light on the most prominent in the section of the most important results reached by suggestions and recommendations, then references, sources and indexes.